Effect of zinc oxide on dispersion and homogeneity of PTFE in NR/NBR rubber matrices / Noorzalila Muhammad Niza and Buvearasan Muniandy - Muhammad Niza, Noorzalila; Muniandy, Buvearasan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
The effect of zinc oxide (ZnO) on the dispersion and homogeneity of polytetrafluoroethylene (PTFE) in the blend of natural and nitrile rubber matrices (NR/NBR) has been investigated. The rubbers and additives were mixed on a two-roll mill and vulcanized by a steam-heated press. The findings from the chemical resistance test showed that the rubber blend with 8 parts per hundred of rubber (phr) of ZnO has better resistance towards organic solvents (acetone, heptane and toluene) and the degree of swelling reduced compared to rubber blend with lower amount of ZnO. Futher investigations on the scanning electron microscopy (SEM) of the rubber compound blend with ZnO showed that the PTFE agglomerations were reduced with particle sizes ranging in the order of 2-8 μm. The decrease in the particles sizes allows an increase in the PTFE surface area with better dispersion and homogeneity in the rubber matrices to be achieved, with reduced solvent uptake by the rubber.